The large scale magnetic field of the G0 dwarf HD 206860 (HN Peg). Issue Volume 9:Issue S302(2013) (7th August 2014) - Saikia, Sudeshna Boro; Jeffers, Sandra V.; Petit, Pascal; Marsden, Stephen; Morin, Julien; Reiners, Ansgar; ,
Abstract: HD 206860 is a young planet (HN Peg b) hosting star of spectral type G0V and it has a potential debris disk around it. In this work we measure the longitudinal magnetic field of HD 206860 using spectropolarimetric data and we measure the chromospheric activity using Ca II H&K, H-alpha and Ca II infrared triplet lines.